Managers Perception On Organisational Management In Islamic Perspective: A Proposed Research Framework - Khairunneezam Mohd Noor; Nur Hanan Abd Aziz; Nurul Nadirah Abu Hassan (Academic International Dialogue (AID) Academy, 2024)
Non-Indexed Publication